Global Heatwaves Dynamics Under Climate Change Scenarios: Multidimensional Drivers and Cascading Impacts - Oluwafemi E. Adeyeri; Wen Zhou; Christopher E. Ndehedehe; Kazeem A. Ishola; Patrick Laux; Akintomide A. Akinsanola; Mame D. B. Dieng; Xuan Wang (Earth's Future)
Abstract Heatwaves are intensifying globally due to climate change. However, the contributions of large‐scale atmospheric processes and land‐atmosphere interactions to heatwave dynamics and their cascading impacts on water resources and human exposure are not fully understood. This study investigates heatwave frequency (HWF) across 50 global regions, spanning historical (1979–2014) and future periods (2025–2060 and 2065–2100) under SSP 370 (regional rivalry) and SSP 585 (fossil‐fuel development) scenarios. Using bias‐corrected general circulation model simulations and reconstructed terrestrial water storage (TWS) data, we quantify the contributions of atmospheric processes to HWF modulation and assess the impacts of HWF and temperature changes on water storage deficits using TWS drought severity index (TWS‐DSI) and standardized temperature index (STI). We show that Western Central Asia exhibits moisture divergence driven by significant positive thermodynamic effects, which correlates with increased HWF. In West Africa, moisture flux divergence at 1,000 hPa accounts for 45% of HWF variability, while relative humidity at 300 hPa explains 58% of HWF changes in East Asia. HWF and STI strongly influence TWS‐DSI, with high STI intensifying TWS deficits. Concurrent high HWF and wet conditions in Western North America are linked to atmospheric blocking and hydrological persistence, highlighting complex illative mechanisms. We project population exposure to HWF to rise tenfold globally by 2100, with regions such as South Asia experiencing over 100% increases due to combined climate and population effects. These findings emphasize the need for tailored adaptation strategies to mitigate heatwave impacts and ensure resilience in a warming world.